Production and characterization of mouse monoclonal antibodies reactive to Chikungunya envelope E2 glycoprotein - Bréhin, Anne-Claire; Rubrecht, Laetitia; Navarro-Sanchez, Martha Erika; Maréchal, Valérie; Frenkiel, Marie-Pascale; Lapalud, Priscilla; Laune, Daniel; Sall, Amadou Alpha; Desprès, Philippe (Virology (New York, N.Y.), 2008)
Chikungunya fever is an arbovirosis of major impact in public health in Asia and Africa. Chikungunya (CHIK) virus is member of the genus Alphavirus and belongs to the Semliki Forest (SF) antigenic complex. We describe for the first time a panel of monoclonal antibodies (MAbs) reactive to CHIK envelope E2 glycoprotein. For the screening of E2-specific MAbs, we expressed a recombinant soluble CHIK E2 protein in Drosophila S2 cells. Analyzed by immunological methods, MAbs 3C3, 3E4, and 8A4 were selected on the basis of their reactivity. Their epitopes are located to the outer surface of CHIK virion. These MAbs have no cross reactivity with related members of SF antigenic complex with the notable exception of Igbo-Ora virus. Anti-CHIK E2 MAbs 3C3, 3E4, and 8A4 should be helpful for studying the biology of CHIK virus and pathogenesis of disease. The combination of 8A4 and 3E4 is suitable for developing a specific antigen-capture ELISA.